The Influence of the Work Environment, Work Motivation and Work Discipline on Employee Performance at The Depok City National Narcotics Agency Office - Riyo Al Mufqi; Ahmad Cik; Melati; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of work environment, work motivation, and work discipline on employee performance of the Depok City National Narcotics Agency. The data of this study used primary data in the form of a questionnaire to 55 individuts. The data analysis technique was using inferential analysis with multiple linear regression and using the Statistical Product and Service Solution (SPSS) version 26.0 program. The results of multiple linear regression analysis show that the variables of Work Environment (X1), Work Motivation (X2), and Work Discipline (X3) have a positive and significant effect on employee performance. The results of this study expect the company to improve the work environment, work motivation, and work discipline that can support employee performance.